2015
DOI: 10.1007/s00380-015-0776-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum neutrophil gelatinase-associated lipocalin concentration reflects severity of coronary artery disease in patients without heart failure and chronic kidney disease

Abstract: Serum neutrophil gelatinase-associated lipocalin (NGAL) is recognized as a useful biomarker for acute kidney injury. Recently, elevated NGAL levels were reported in patients with heart failure and cardiac events, but the association between serum NGAL and severity of coronary artery disease (CAD) has not been investigated adequately. This study aimed to evaluate the association between serum NGAL concentration and CAD severity in patients without heart failure and chronic kidney disease. Two-hundred thirteen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…In fact, urinary and plasma lipocalin‐2 levels are positively associated with increased N‐terminal pro‐brain natriuretic peptide, the New York Heart Association class, and the left ventricular internal end‐diastolic dimension in patients with chronic heart failure . Plasma lipocalin‐2 levels correlate with heart failure severity and predict major adverse cardiovascular events in critically ill patients . The present study demonstrates that npLcn2 represents a more specific marker for cardio‐renal metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, urinary and plasma lipocalin‐2 levels are positively associated with increased N‐terminal pro‐brain natriuretic peptide, the New York Heart Association class, and the left ventricular internal end‐diastolic dimension in patients with chronic heart failure . Plasma lipocalin‐2 levels correlate with heart failure severity and predict major adverse cardiovascular events in critically ill patients . The present study demonstrates that npLcn2 represents a more specific marker for cardio‐renal metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…12 Clinical studies have demonstrated that levels of circulating NGAL are associated with the degree of inflammatory process in patients with coronary artery disease where NGAL levels are higher in patients with acute coronary syndrome compared with patients with stable coronary artery disease, and elevated serum NGAL as an independent risk factor for a high SYNTAX score. 19,20,27 Furthermore, high plasma NGAL levels are associated with poor prognosis in patients with myocardial infarction and in the general population. 16e18 The present study examined the relationship between NGAL mRNA expression in plaque and the percentage of carotid artery stenosis and did not find any significant difference in NGAL mRNA expression in patients with stenosis grade of <90% and !90%.…”
Section: Discussionmentioning
confidence: 99%
“…These high levels of NGAL may be explained in part by the renal failure observed in a large number of HF patients (79). However, several studies have showed that NGAL was a predictor of CV incident even in the absence of renal dysfunction (80)(81)(82).…”
Section: Ngal In Myocardial Infarction and Heart Failurementioning
confidence: 99%